2007
DOI: 10.1159/000101568
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Adaptation to Anemia and Red Blood Cell Transfusion in Premature Infants Requiring Ventilation Support in the 1st Postnatal Week

Abstract: Background: Although transfusion practice in very premature infants is becoming more restrictive, little is known about myocardial adaptation to anemia during the 1st postnatal week. Objectives: To determine the central hemodynamic effects of anemia and red blood cell transfusion in very preterm infants undergoing intensive care. Methods: Twenty-nine neonates of less than 30 weeks gestational age were treated for respiratory distress syndrome, following a strict protocol. Echocardiographies were performed at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Our results are supported by the fi ndings of the conventional vascular Doppler studies in anemic neonates: the more severe anemia is, the higher is the myocardial contractility [6] .…”
Section: Pre-iut Vs Control (Anemia Vs Non-anemia)supporting
confidence: 85%
See 1 more Smart Citation
“…Our results are supported by the fi ndings of the conventional vascular Doppler studies in anemic neonates: the more severe anemia is, the higher is the myocardial contractility [6] .…”
Section: Pre-iut Vs Control (Anemia Vs Non-anemia)supporting
confidence: 85%
“…Changes in V max and amount of blood fl ow have been proven in anemia [4,8,9,13,16,19,20,24,30] . The additional acute massive volume burden of IUT to the fetal heart is supposed to further change the hemodynamic state [6,22,30] .…”
Section: Introductionmentioning
confidence: 99%
“…This maintained RV performance has been described in both healthy neonates [4] and infants with respiratory distress syndrome [5] . In preterm infants, anemia and blood cell transfusion have been shown to have an influence on ventricular function [36] . Subhedar and Shaw [37] demonstrated that premature infants with bronchopulmonary dysplasia (BPD) had higher echocardiographically-derived pulmonary artery pressures than did premature infants without BPD.…”
Section: Discussionmentioning
confidence: 99%
“…If our measurements had comprised not only ventricular and annular but also atrial ROIs, the relationship between the atrial myocardial function and the flow pattern of the DV speculated on here probably would have become obvious. The longitudinal PS reveals a significantly negative correlation with the PI in the UA in the right ventricle, being in accordance with an increased contractility in anemia [3,17]. The RV seems to compensate for stress.…”
Section: Correlation Between Vascular Doppler and Tissue Doppler Paramentioning
confidence: 77%